Demographic and Socio-economic Factors Affecting Antenatal Care Services Utilization in Nepal - Acharya, Sunil Kumar (Journal of Development and Administrative Studies, 2018)
In Nepal, Antenatal care (ANC) services seeking behavior has improved since the 1990s. More pregnant women are seeking the services now than ever. Still a relatively high percentage does not seek even a onetime ANC care and the percentage of women who seek 4 or more ANC care from a skilled service provider is still low. Research in developing countries shows that various demographic, social and economic factors influence the utilization of ANC services and the number of times the care is sought by pregnant women. This paper examines the likelihood of utilization of ANC services 4 or more times in relation to women’s demographic, social and economic status in Nepal. The 2011 Nepal Demographic and Health Survey (NDHS) data set has been utilized by applying bivariate logistics regression analysis technique to examine the effects of these variables in 4 or more ANC use in Nepal. The analysis findings show large variations and gaps in the utilization of ANC care based on demographic, social and economic status of women. Against this finding, the study recommends implementation of appropriate policy and program measures by the government and other agencies to address the existing variations and gaps in ANC services utilization among different sub-groups of women in Nepal. Further research studies focusing on the existing barriers in ANC services utilization need to be conducted in Nepal especially among the women who are disadvantaged and marginalized. The Journal of Development and Administrative Studies (JODAS) Vol. 24 (1-2), pp. 71-87